Development of Coaching Model in Pumping-HR Based Human Resource Development Model - Ramly, Amir Tengku; Irawan, Andi; Warcito, Warcito (Jurnal Manajemen (Edisi Elektronik), 2021)
Coaching is a partner of development in which a coach supports a learner in achieving a specific personal or professional goal by training and counselling. The pumping HR Model is one of the HR development models based on the iceberg theory, which is divided into the areas of the unconscious (unconscious region), pre-conscious (pre-conscious region) and conscious (conscious region). The pumping HR Model places the unconscious as a function of the heart, the pre-conscious as a function of the brain and the conscious as a sensory function of human resources (HR). In practice, Pumping HR Model touches on 3 basic components of human resource development, namely character development, competency development and behaviour development. This research goal is the purpose of this study is to prove that the Pumping HR model can be used as a model in the coaching process. The method used is qualitative descriptive & Integrating theory. Research data were obtained through a Focus Group Discussion (FGD) and post-workshop questionnaire.  The results of this research: Pumping HRM Coach is unique and can be one of the human resource development models with a coaching approach.